2017
DOI: 10.1080/20442041.2017.1294348
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of ultraviolet sunscreen compounds (mycosporine-like amino acids) by the heterotrophic freshwater ciliateBursaridiumliving in alpine lakes

Abstract: Ciliates in shallow alpine lakes are exposed to high levels of incident solar ultraviolet radiation (UVR). We observed the presence of specific sunscreen compounds, the mycosporine-like amino acids (MAAs), in several populations of Bursaridium, a relatively large ciliate species found in such lakes. The populations from 3 highly UV transparent lakes revealed the presence of 7 MAAs (MG, SH, PR, PI, AS, US, and PE) in total concentrations of 3.6–52.4 10−5 μg μg−1 dry weight (DW) per individual, whereas in one gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 60 publications
(79 reference statements)
1
16
0
Order By: Relevance
“…), the acquisition of sunscreen compounds (mycosporine‐like amino acids; Sonntag et al. , ), and/or effective DNA photorepair processes (Sanders et al. ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…), the acquisition of sunscreen compounds (mycosporine‐like amino acids; Sonntag et al. , ), and/or effective DNA photorepair processes (Sanders et al. ).…”
mentioning
confidence: 99%
“…Under UVR exposure, the motility and cell division/reproduction rates of ciliates can be significantly affected (Giese 1945;Giese et al 1963;H€ ortnagl and Sommaruga 2007;Sgarbossa et al 1995;Sommaruga et al 1999). However, ciliate species respond individually to high UVR levels including avoidance (shading; Slaveykova et al 2016), densely packed cell matter around the nuclei (algal symbionts; Sommaruga and Sonntag 2009;Summerer et al 2009;Sonntag et al 2011b), the acquisition of sunscreen compounds (mycosporine-like amino acids; Sonntag et al 2007Sonntag et al , 2017, and/or effective DNA photorepair processes (Sanders et al 2005). For example, photoenzymatic repair (PER) was reported in Paramecium (Sutherland et al 1967;Takahashi et al 2005;Zaar 1968) and experiments with Glaucoma and Cyclidium revealed that this mechanism was strongly temperature-dependent and significantly more effective at higher temperatures (Sanders et al 2005).…”
mentioning
confidence: 99%
“…Mycosporine‐like amino acids were identified in only one heterotrophic ciliate of several tested by Sonntag et al. (), and seemed related primarily, though perhaps not completely to the amount of MAAs present in the seston of an alpine lake. The relationship between pigments and photoprotection is complex (Marangoni et al.…”
Section: Discussionmentioning
confidence: 94%
“…Stentorin pigments and MAAs have been reported in ciliates, but mostly in pigmented individuals and/or those possessing algal endosymbionts (Modenutti et al 1998(Modenutti et al , 2005Sommaruga et al 2006;Sonntag et al 2007), neither of which are present in P. acutum. Mycosporine-like amino acids were identified in only one heterotrophic ciliate of several tested by Sonntag et al (2017), and seemed related primarily, though perhaps not completely to the amount of MAAs present in the seston of an alpine lake. The relationship between pigments and photoprotection is complex (Marangoni et al 1997), but with limited photoprotection, the survival of P. acutum without PRR following single, but not repeated UV exposure is most likely due to NER.…”
Section: Repeated Exposure To Uvbmentioning
confidence: 96%
“…Members of the genus Urotricha Claparède and Lachmann, 1859 represent some of the most common planktonic ciliates in freshwater systems worldwide, including temperate and remote lakes, and reservoirs (e.g., Weisse et al, 1990;Sonntag et al, 2006Sonntag et al, , 2017Sichrowsky et al, 2014;Posch et al, 2015;Kammerlander et al, 2016;Šimek et al, 2019). Urotricha species often dominate ciliate communities and co-occur with other small prostomatids, such as Balanion planctonicum, halteriids, and diverse oligotrichs, e.g., Rimostrombidium species.…”
Section: Introductionmentioning
confidence: 99%